Role of Cytokeratin-7 in the pathogenesis of odontogenic cysts - an immunohistochemical study - Saluja, Pulin (Med Pharm Rep, 2019)
INTRODUCTION: Odontogenic cysts are distinct entities and quite a common occurrence in the jaw bones. These are individual lesions which arise from the same odontogenic apparatus but with varying pathogenesis. Cytokeratins are integral components in tooth development and are expressed across the odontogenic tissues in physiological and pathological states. AIM: To elucidate the role of cytokeratin-7 in the pathogenesis of odontogenic cysts by immunohistochemistry. METHOD: Cytokeratin-7 (CK-7) was assessed in 39 cases of odontogenic lesions retrieved from the archival files which included 15 cases of dentigerous cysts (DC), 12 cases of odontogenic keratocysts (OKC) and 12 cases of radicular cysts (RC) and also 8 cases of control specimens. STATISTICAL ANALYSIS: Results obtained were statistically analyzed using chi-square test to assess the association between different odontogenic cysts used in this study and Cytokeration-7 staining. The difference was considered to be of statistical significance if the p value was ≤ 0.05. RESULTS: CK7 expression was maximum in dentigerous cycts (66.66%) followed by radicular cysts (41.66%) and odontogenic keratocysts (16.6%). On evaluation of staining and expression pattern, highest positivity is shown in dentigerous cysts and the positivity is seen in suprabasal (60%) and superficial layers (40%) whereas radicular cysts and odontogenic keratocysts showed positivity in superficial and spinous layers. CONCLUSION: Cytokeratin-7 expression correlates with the degree of differentiation of the epithelium. So the cysts with a well-differentiated epithelium (RC and DC) express CK-7, while the cysts with a less well-differentiated epithelium (OKC) show slight positivity. Thus it can be useful to differentiate OKC from DC and RC.